A high-viscosity asphalt concrete with more crushed stones
By developing SHAC-13 type multi-gravel high-viscosity modified asphalt mixture, combined with high-viscosity modified asphalt and modified aggregate, the problem of insufficient rut resistance and durability of existing asphalt pavements at high temperatures has been solved, and the stability and performance of the asphalt mixture has been improved.
Patent Information
- Application Number
- CN202410212758.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-02-27
AI Technical Summary
The existing asphalt pavement has ruts and water damage before fatigue cracking occurs, and the existing design is difficult to effectively control these early diseases, and the high-temperature performance and durability of the asphalt mixture are insufficient.
A multi-gravel high-viscosity asphalt concrete based on SHAC-13 type multi-gravel high-viscosity modified asphalt mixture was developed. Through the combination of high-viscosity modified asphalt, modified coarse aggregate and modified fine aggregate, the surface modification treatment was carried out using alkynyl-coupled monomer and azide-coupled monomer to enhance the interface bonding between the aggregate and the asphalt.
It significantly improves the high-temperature rutting resistance and durability of the asphalt mixture, enhances the structural stability of the mixture and the asphalt film thickness, and improves the low-temperature performance and crack resistance of the asphalt mixture.
Smart Images

Figure CN118005322B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of research and development of high-gravel asphalt concrete, in particular to high-gravel high-viscosity asphalt concrete. Background Art
[0002] In my country, semi-rigid base asphalt pavement is mainly used as a typical structure, with the design deflection value as the structural design control index, and the elastic layered system theory under double-circle uniformly distributed load is used to calculate the pavement structure thickness. Conceptually, the current design takes pavement fatigue cracking as the main disease mode, but the reality is that asphalt pavement has two other typical early diseases - rutting and water damage - long before fatigue cracking occurs, and the design has not played a role in controlling the disease. From past experience, it can be seen that hard asphalt concrete is superior to other types of asphalt concrete in terms of anti-rutting performance. In addition, from an economic point of view, the use of hard asphalt mixture can reduce the cost of the project. Natural asphalt (such as Trinidad Lake Asphalt TLA) has been used in some domestic highway projects. Fiber, as a high-strength, durable and lightweight reinforcing material, can improve the mechanical properties and service life of asphalt pavement. At present, wood fiber, polymer fiber and mineral fiber are widely used in asphalt pavement projects, among which polymer fiber has been widely used in some important sections and bridge deck pavement. According to different environmental, material and technical requirements, there are now a wide variety of anti-rutting agents on the market, such as foreign PR and my country's Rutting King.
[0003] Asphalt, as an important binder of pavement, has an important influence on the durability of pavement. In the aging process of asphalt mixture, it mainly refers to the aging of asphalt. The aging of asphalt will cause the asphalt to harden and decrease its adhesion, which will reduce the overall performance of asphalt pavement. In the plastic deformation process of asphalt pavement, asphalt is also an important factor affecting the asphalt pavement's resistance to external load damage. In fatigue tests, the quality of asphalt performance also directly affects the fatigue durability of asphalt mixture. Therefore, the selection of binder plays a very important role in the durability of asphalt pavement. Since PE, SBR, and rubber powder modified asphalt have certain deficiencies in high and low temperature performance compared with SBS modified asphalt, the current design mainly adopts SBS modified asphalt, which has good viscoelasticity and can take into account high and low temperature performance. However, the current design requirements are generally based on ID and IC type SBS modified asphalt, and the softening point requirement of not less than 60℃ is relatively low. For the hot summer area, this indicator cannot fully meet the high temperature driving requirements of the pavement. In addition, the type of asphalt mixture is relatively single, mainly AC and SMA, and it is difficult to increase its oil-stone ratio with traditional modified asphalt. Increasing the thickness of the asphalt film will inevitably improve the durability of the asphalt pavement. The thicker the asphalt film, the higher the proportion of free asphalt in the asphalt film. The proportion of free asphalt determines the failure mechanism of the asphalt-aggregate interface. The lower the proportion of free asphalt, the greater the proportion of adhesion failure in the interface failure process; the higher the proportion of free asphalt, the greater the proportion of cohesion failure in the interface failure process. Properly increasing the content of free asphalt can improve the fatigue performance of the mixture. Summary of the invention
[0004] In order to improve the performance of asphalt and ensure the mixing workability, porosity, low temperature performance and durability of asphalt mixture, and combined with the experimental experience of high-toughness ultra-thin overlay technology, the present invention has developed a multi-gravel high-viscosity asphalt concrete based on SHAC-13 type multi-gravel high-viscosity modified asphalt mixture, which can provide a reliable and stable high-performance pavement structure layer.
[0005] A high-viscosity asphalt concrete with more crushed stone, the raw materials used in the concrete are SHAC-13 type high-viscosity modified asphalt mixture with more crushed stone, which includes high-viscosity modified asphalt, modified coarse aggregate Ca-alkynyl, modified fine aggregate Fa-N3 and mineral powder;
[0006] The preparation method of high-viscosity modified asphalt is as follows: ID-type SBS modified asphalt is heated to a fluid state, 0.5-8wt% of catechol-terminated cross-linking monomer is added during the stirring process, and the high-viscosity modified asphalt is first sheared and then stirred to prepare the high-viscosity modified asphalt.
[0007] Preferably, the method for preparing the high-viscosity asphalt concrete with more crushed stones comprises the following steps:
[0008] Step 1: Prepare SHAC-13 type high-viscosity modified asphalt mixture with more crushed stones;
[0009] Step 2: Prepare modified coarse aggregate Ca-alkynyl, the modification method is: use alkynyl coupling monomer to modify the surface of coarse aggregate, the inorganic end of alkynyl coupling monomer generates Si-OH through hydrolysis, which undergoes polycondensation reaction on the surface of coarse aggregate to form a polysiloxane coupling layer, forming chemical adsorption, hydrogen bonds and covalent bonds; the flexible organic end and alkynyl functional group of alkynyl coupling monomer are modified on the surface of coarse aggregate at the same time;
[0010] Step 3: Prepare modified fine aggregate Fa-N3, the modification method of which is: use azide coupling monomer to perform surface modification on the fine aggregate, the inorganic-philic end of the azide coupling monomer generates Si-OH through hydrolysis, which undergoes polycondensation reaction on the surface of the fine aggregate to generate a polysiloxane coupling layer, forming chemical adsorption, hydrogen bonds and covalent bonds; the flexible organic-philic end and azide functional group of the azide coupling monomer are simultaneously modified on the surface of the fine aggregate;
[0011] Step 4: Using Cu(Ⅰ)-catalyzed alkynyl-azide cycloaddition click reaction, the fine aggregate is modified onto the surface of the coarse aggregate to prepare the premixed aggregate;
[0012] Step 5: Heat the high-viscosity modified asphalt to 160-180°C, add premixed aggregate, mix for 60-120 seconds, then add mineral powder, mix for 45-70 seconds to obtain high-viscosity asphalt concrete with more crushed stone.
[0013] Preferably, the synthesis method of the alkynyl coupling monomer is: using triethoxysilane and undecenyl alcohol as raw materials and chloroplatinic acid as a catalyst, hydroxytriethoxysilane is synthesized by a hydrosilylation reaction; using the Williamson ether synthesis method, sodium hydride is used to catalyze the etherification reaction between 3-bromopropyne and hydroxytriethoxysilane to prepare the alkynyl coupling monomer.
[0014] Preferably, the synthesis method of the azide coupling monomer is: using the Williamson ether synthesis method, 1,4-dibromobutane and hydroxytriethoxysilane undergo an etherification reaction catalyzed by sodium hydride to generate bromotriethoxysilane; based on the nucleophilic substitution reaction mechanism, bromotriethoxysilane is used as a raw material and undergoes an azidation reaction with sodium azide to prepare the azide coupling monomer.
[0015] Preferably, the preparation method of the catechol-terminated cross-linking monomer is: utilizing the Schiff base reaction mechanism, using 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane as a raw material, and using 3,4-dihydroxybenzaldehyde as a capping agent to prepare the catechol-terminated cross-linking monomer.
[0016] Preferably, the mineral aggregate gradation ratio in the high-viscosity asphalt concrete with high crushed stone is: coarse aggregate with a particle size of 4.75 mm to 16 mm: fine aggregate with a particle size of 0.075 mm to 4.75 mm: mineral powder = 63%: 31.9%: 5.1%;
[0017] Preferably, the oil-to-stone ratio in the high-gravel high-viscosity asphalt concrete is 6.0.
[0018] The above-mentioned high-viscosity asphalt concrete with more crushed stones can be used in pavement engineering.
[0019] Compared with the prior art, the present invention has the following beneficial technical effects:
[0020] The present invention: firstly synthesizes an alkynyl coupling monomer, an azide coupling monomer, and a catechol-terminated cross-linking monomer, and uses the catechol-terminated cross-linking monomer to perform high-viscosity modification treatment on asphalt;
[0021] Then, the coarse aggregate was surface-modified using alkynyl coupling monomers, the fine aggregate was surface-modified using azide coupling monomers, and the fine aggregate was modified onto the surface of the coarse aggregate using Cu(Ⅰ)-catalyzed alkynyl-azide cycloaddition click reaction to prepare the premixed aggregate.
[0022] The premixed aggregate: on the one hand, reduces the spatial rotation and secondary rearrangement effect of the aggregate under wheel load, and on the other hand, the surface-modified flexible organic end is cross-linked with the asphalt molecules to produce a strong physical adsorption effect, thereby improving the interfacial adhesion between the aggregate and the asphalt;
[0023] The high-quality asphalt concrete of the present invention, which is based on the research of skeleton compaction and high-viscosity modification, can greatly improve the stability of the asphalt mixture structure by enhancing the skeleton embedding effect in the mixture and adopting a higher grade of asphalt binder, reduce the spatial rotation and secondary rearrangement effect of aggregates under the action of wheel loads, and ensure that the mixture is fully compacted. Under the premise of providing a reliable and stable high-performance pavement structure layer through the combined action of skeleton grading and special high-viscosity modified asphalt. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A synthetic route for alkynyl coupling monomers;
[0025] Figure 2 It is a synthetic route for azide coupling monomers;
[0026] Figure 3 It is a synthetic route for catechol-terminated cross-linking monomers;
[0027] Figure 4 It is a bar chart of the high and low temperature performance test results of different types of asphalt mixtures. DETAILED DESCRIPTION
[0028] Embodiment 1:
[0029] A high-viscosity asphalt concrete with more crushed stone, using SHAC-13 type high-viscosity modified asphalt mixture with more crushed stone as raw material, comprising high-viscosity modified asphalt, modified coarse aggregate Ca-alkynyl, modified fine aggregate Fa-N3 and mineral powder;
[0030] The technical indicators of the aggregates and mineral powder used meet the requirements specified in the "Code for Construction and Quality Acceptance of Urban Road Engineering" CJJ1-2008;
[0031] Based on the skeleton dense structure of mineral aggregate gradation, the mineral aggregate gradation in SHAC-13 type high-viscosity modified asphalt mixture with multiple crushed stones was tested and studied. Since the use of high-viscosity modified asphalt will inevitably increase the amount of asphalt and increase the thickness of the asphalt film, the asphalt mixture is a skeleton structure. The skeleton dense structure test method - VCADRU method was used for verification. The amount of filler was appropriately reduced to ensure that the amount of asphalt mortar was properly filled, to avoid excessive fine aggregates from "expanding" the gaps in the asphalt mixture, and to retain an appropriate void ratio (about 4%); and the performance index requirements of high-viscosity modified asphalt were determined in combination with the ambient temperature and load requirements, and the durability of the mixture was improved by comprehensively determining the high asphalt dosage;
[0032] And a comparative experiment was conducted on AC-13C traditional asphalt mixture and SAC-13 multi-gravel asphalt mixture;
[0033] The design results of the mineral aggregate gradation composition and the asphalt-to-rock ratio of the above-mentioned SHAC-13 type high-viscosity modified asphalt mixture, AC-13C traditional asphalt mixture and SAC-13 high-viscosity asphalt mixture are shown in Table 1 below;
[0034] Table 1 Mineral aggregate gradation composition and asphalt-rock ratio of asphalt mixture
[0035]
[0036]
[0037] Note: SBS ID is ID type SBS modified asphalt;
[0038] The preparation method of high viscosity modified asphalt is as follows: ID type SBS modified asphalt is heated to a fluid state, and 3.5wt% of catechol end-capping crosslinking monomer (the chemical synthesis route of which is as follows) is added during the stirring process. Figure 3 As shown), firstly sheared at 5000r / min and 180℃ for 2h, then developed and stirred at 700r / min and 165℃ for 1.5h to make high-viscosity modified asphalt, and its performance test results are shown in Table 2 below;
[0039] Table 2 Performance test results of high viscosity modified asphalt and ID type SBS modified asphalt
[0040] Needle penetration 0.1mm Softening point / ℃ Elongation (5℃) / cm Dynamic viscosity / Pa·s High viscosity modified asphalt 45 90 42 65400 ID type SBS modified asphalt 53 72 43 —
[0041] Embodiment 2:
[0042] A method for preparing high-viscosity asphalt concrete with more crushed stones comprises the following steps:
[0043] Step 1: Prepare SHAC-13 type high-viscosity modified asphalt mixture with more crushed stones;
[0044] Among them, the grading ratio of mineral materials is: coarse aggregate (particle size range is 4.75mm~16mm): fine aggregate (particle size range is 0.075mm~4.75mm): mineral powder = 63%: 31.9%: 5.1%;
[0045] The oil-stone ratio is 6.0;
[0046] Step 2: Prepare modified coarse aggregate Ca-alkynyl, the specific experimental process is as follows:
[0047] (1) Prepare a mixed solvent of anhydrous ethanol and deionized water, add an alkynyl coupling monomer (whose chemical synthesis route is as follows Figure 1 As shown), a mixed solution is obtained;
[0048] Wherein, m(alkyne coupling monomer):m(deionized water):m(anhydrous ethanol)=8:42:50;
[0049] (2) The mixture was heated to 60°C and the pH value was maintained at 9, stirred for 1 hour, cooled to room temperature and allowed to stand for 1 hour;
[0050] (3) Soaking the coarse aggregate (with a particle size range of 4.75 mm to 16 mm) in the mixed solution for 1 hour, taking out the coarse aggregate and curing it at 150° C. for 2 hours to obtain modified coarse aggregate Ca-alkynyl;
[0051] Step 3: Prepare modified fine aggregate Fa-N3. The specific experimental process is as follows:
[0052] (1) Prepare a mixed solvent of anhydrous ethanol and deionized water, add an azide coupling monomer (whose chemical synthesis route is as follows Figure 2 As shown), a mixed solution is obtained;
[0053] Wherein, m(azide coupling monomer):m(deionized water):m(anhydrous ethanol)=10:45:45;
[0054] (2) The mixture was heated to 60°C and the pH value was maintained at 10, stirred for 1 hour, cooled to room temperature and allowed to stand for 1 hour;
[0055] (3) Soaking fine aggregate (particle size ranges from 0.075 mm to 4.75 mm) in the mixed solution for 1 h, taking out the fine aggregate and curing it at 140 °C for 2 h to obtain modified fine aggregate Fa-N3;
[0056] Step 4: Using Cu(Ⅰ)-catalyzed alkynyl-azide cycloaddition click reaction, the fine aggregate is modified onto the surface of the coarse aggregate to prepare the premixed aggregate. The specific experimental process is as follows: the modified fine aggregate Fa-N3 and the modified coarse aggregate Ca-alkynyl are immersed in methanol and stirred for 0.5 h, then 7 wt% of cuprous iodide and dimethylformamide (m(cuprous iodide):m(dimethylformamide)=1:9) are added, and the mixture is reacted at 70°C for 3 h to obtain the premixed aggregate;
[0057] Step 5: Heat the high-viscosity modified asphalt to 170°C, add premixed aggregate, mix for 90 seconds, then add mineral powder and mix for 60 seconds to obtain high-viscosity asphalt concrete with more crushed stone.
[0058] Embodiment 3:
[0059] Preparation of alkynyl coupling monomers, such as Figure 1 As shown, the synthesis process is as follows:
[0060] The first step: using triethoxysilane and undecenyl alcohol as raw materials and chloroplatinic acid as a catalyst, synthesizing hydroxytriethoxysilane through a hydrosilylation reaction;
[0061] The specific experimental operation for synthesizing hydroxytriethoxysilane is as follows: 10 mL of undecenyl alcohol and 3 drops of chloroplatinic acid-isopropanol solution (the preparation method is: 0.3 g of H2PtCl·6H2O is added to 10 mL of anhydrous isopropanol, fully stirred, and left to stand in the dark for 1 day after all dissolved) are added to a three-necked flask equipped with a stirrer, a reflux condenser, and a dropping funnel, stirring is started, and heating is performed. When the temperature rises to 80°C, 9.5 mL of triethoxysilane is added dropwise using a dropping funnel, and the dropping rate is controlled (1d / 2s). After the addition is completed, the reaction is stirred at a temperature of 90°C for 3 hours, and low-boiling-point materials are removed by reduced pressure distillation to obtain hydroxytriethoxysilane;
[0062] Step 2: Using the Williamson ether synthesis method, 3-bromopropyne and hydroxytriethoxysilane are reacted to form an ether by sodium hydride to prepare an alkynyl coupling monomer;
[0063] The specific experimental operation of synthesizing the alkynyl coupling monomer is as follows: first, 1.5 g of sodium hydride is dissolved in 60 mL of anhydrous tetrahydrofuran under ice bath conditions, and then 40 mL of anhydrous tetrahydrofuran in which 10 g of hydroxytriethoxysilane is dissolved is added dropwise to the solution, and the dropping rate is controlled (1 d / 2 s). Then, 2.6 mL of 3-bromopropyne is added dropwise to the mixed solution, and the dropping rate is controlled (1 d / 5 s). After the addition is completed, the reaction is stirred at room temperature for 12 h, and the reaction product is placed in a column of neutral alumina, diatomaceous earth and activated carbon to remove byproducts and unreacted sodium hydride, the liquid is collected and rotary evaporated to remove tetrahydrofuran, and purified by column with ethyl acetate: petroleum ether (V / V=1 / 6) to obtain the alkynyl coupling monomer;
[0064] 1 H NMR (400MHz, CDCl3, δ, ppm): 0.71-0.76 (t, 2H), 1.20-1.24 (t, 9H), 1.25-1.35 (m, 14H), 1.4 8-1.61 (m, 4H), 2.50-2.52 (t, 1H), 3.54-3.57 (t, 2H), 3.78-3.82 (m, 6H), 4.16-4.17 (d, 2H).
[0065] Preparation of azide coupling monomers, such as Figure 2 As shown, the synthesis process is as follows:
[0066] The first step: using the Williamson ether synthesis method, 1,4-dibromobutane and hydroxytriethoxysilane are catalyzed by sodium hydride to produce etherification reaction to generate bromotriethoxysilane;
[0067] The specific experimental operation of synthesizing bromotriethoxysilane is as follows: first, 1.5 g of sodium hydride is dissolved in 60 mL of anhydrous tetrahydrofuran under ice bath conditions, and then 40 mL of anhydrous tetrahydrofuran containing 10 g of hydroxytriethoxysilane is added dropwise to the solution at a controlled dripping rate (1 d / 2 s), and then 5 mL of 1,4-dibromobutane is added dropwise to the mixed solution at a controlled dripping rate (1 d / 5 s). After the addition is completed, the mixture is stirred at room temperature for 10 h to react, and the reaction product is placed in a column of neutral alumina, diatomaceous earth and activated carbon to remove byproducts and unreacted sodium hydride, and the liquid is collected and rotary evaporated to remove tetrahydrofuran and 1,4-dibromobutane, and purified by column with ethyl acetate: petroleum ether (V / V=4 / 5) to obtain bromotriethoxysilane;
[0068] Step 2: Based on the nucleophilic substitution reaction mechanism, bromotriethoxysilane is used as a raw material to undergo an azidation reaction with sodium azide to prepare an azide coupling monomer;
[0069] The specific experimental operation of synthesizing the azide coupling monomer is as follows: 7.02 g of bromotriethoxysilane and 1.46 g of sodium azide are dissolved in 100 mL of N,N-dimethylformamide, and the mixture is refluxed at 80°C for 12 h, extracted with ether, and the organic phases are combined, washed with distilled water, dried over anhydrous magnesium sulfate, and the solvent is removed by rotary evaporation. The mixture is purified by column using petroleum ether as an eluent to obtain the azide coupling monomer;
[0070] 1 H NMR (400MHz, CDCl3, δ, ppm): 0.64-0.68 (t, 2H), 1.19-1.23 (t, 9H), 1.23-1.33 (m, 14H), 1.51-1.79(m, 8H), 3.30-2.33(t, 2H), 3.40-3.44(m, 4H), 3.78-3.84(m, 6H).
[0071] The invention discloses a catechol-terminated cross-linking monomer, wherein the synthesis process is as follows: using the Schiff base reaction mechanism, using 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane as a raw material, and using 3,4-dihydroxybenzaldehyde as a capping agent, to prepare the catechol-terminated cross-linking monomer;
[0072] The specific experimental operation of synthesizing catechol-terminated cross-linking monomer is as follows: under the protection of nitrogen, 2.76g 3,4-dihydroxybenzaldehyde and 40mL anhydrous ethanol are added to a three-necked flask. After complete dissolution, 2.75mL 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane dissolved in 30mL anhydrous ethanol is added dropwise to the three-necked flask using a dropping funnel. The dropping rate (1d / 3s) is controlled. At the same time, anhydrous magnesium sulfate is added to absorb the water generated in the reaction. After the addition is completed, the reaction is carried out at 45°C for 8h, the magnesium sulfate is removed by filtration at normal pressure, and the filtrate is collected and evaporated to remove the solvent to obtain the catechol-terminated cross-linking monomer;
[0073] 1 H NMR (400MHz, CDCl3, δ, ppm): 0.11 (s, 12H), 0.79-0.84 (t, 4H), 1.62-1.70 (m, 4H), 3.46-3.49 (t, 4H), 6.81-7.14 (m, 6H), 8.24 (s, 2H).
[0074] Performance test experiment:
[0075] (I) According to the "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" JTG E20-2011, a rutting test was conducted to study the high temperature stability of SHAC-13 type high-viscosity modified asphalt mixture with more crushed stone, AC-13C traditional asphalt mixture and SAC-13 asphalt mixture with more crushed stone. The rutting test results are shown in Table 3 below.
[0076] Table 3 Rutting test results of asphalt concrete specimens
[0077]
[0078] The following conclusions were drawn by analyzing the rutting test results in Table 3:
[0079] (1) When the asphalt performance is the same and only the mineral aggregate gradation is changed, due to the high proportion of SAC-13 coarse aggregate, the 60°C dynamic stability of the asphalt mixture can be appropriately improved by increasing the amount of mineral powder while ensuring density. However, as the test environment temperature increases, the asphalt tends to be a "plastic flow body" when it is about to reach the softening point temperature, and irreversible deformation is formed under repeated load. The high temperature rutting resistance problem cannot be solved by adjusting the mineral aggregate gradation alone;
[0080] (2) The SHAC-13 type high-viscosity modified asphalt mixture with more crushed stone independently developed by the present invention has significantly improved anti-rutting performance compared with traditional modified asphalt mixture. As the test environment temperature increases, the dynamic stability has a significant downward trend. At 70°C, it is slightly lower than the value of ≮2800 times / mm required by the specification, but it is 3 to 4 times higher than that of traditional modified asphalt mixture, and the deformation amount is significantly reduced.
[0081] (ii) According to the T 0728-2000 asphalt mixture bending creep test, the low temperature performance of SHAC-13 type high-viscosity modified asphalt mixture with more crushed stone, AC-13C traditional asphalt mixture and SAC-13 asphalt mixture with more crushed stone was studied. The experimental results are shown in Table 4 below;
[0082] Table 4 Results of low temperature bending test of asphalt concrete specimens
[0083] Mixture type Low temperature bending failure strain (με) AC-13C 2536 SAC-13 2682 SHAC-13 3213
[0084] According to the test data in Table 3 and Table 4, Figure 4 , through analysis Figure 4 The following conclusions were drawn:
[0085] (1) The skeleton structure of the SHAC-13 type high-viscosity modified asphalt mixture with multiple crushed stones realizes the interlocking effect between aggregates, which, together with the effect of high-viscosity modified asphalt, can significantly improve the high-temperature rutting resistance of the asphalt mixture;
[0086] (2) The thickness of the asphalt film is significantly increased compared with traditional asphalt mixtures, which can improve the durability of asphalt mixtures. The great increase in the dynamic viscosity of asphalt at 60°C can significantly increase the amount of asphalt used. The rich asphalt system in the mixture system ensures the toughness and low-temperature crack resistance of the asphalt mixture, which is much better than the low-temperature performance of traditional mixtures. The dense skeleton structure ensures the porosity of the asphalt mixture and can avoid water damage caused by rainwater infiltration.
Claims
1. A high-viscosity asphalt concrete with more crushed stones, characterized in that: The raw materials used in the concrete are SHAC-13 type multi-crushed stone high-viscosity modified asphalt mixture, which includes high-viscosity modified asphalt, modified coarse aggregate Ca-alkynyl, modified fine aggregate Fa-N3 and mineral powder; The preparation method of high-viscosity modified asphalt is as follows: ID-type SBS modified asphalt is heated to a fluid state, 0.5-8wt% of catechol end-capping cross-linking monomer is added during the stirring process, and the mixture is first sheared and then stirred to prepare the high-viscosity modified asphalt; The method for preparing the high-viscosity asphalt concrete with more crushed stones comprises the following steps: Step 1: Prepare SHAC-13 type high-viscosity modified asphalt mixture with more crushed stones; Step 2: Prepare modified coarse aggregate Ca-alkynyl, the modification method is: use alkynyl coupling monomer to modify the surface of coarse aggregate, the inorganic end of alkynyl coupling monomer generates Si-OH through hydrolysis, which undergoes polycondensation reaction on the surface of coarse aggregate to form a polysiloxane coupling layer, forming chemical adsorption, hydrogen bonds and covalent bonds; the flexible organic end and alkynyl functional group of alkynyl coupling monomer are modified on the surface of coarse aggregate at the same time; Step 3: Prepare modified fine aggregate Fa-N3, the modification method of which is: use azide coupling monomer to perform surface modification on the fine aggregate, the inorganic-philic end of the azide coupling monomer generates Si-OH through hydrolysis, which undergoes polycondensation reaction on the surface of the fine aggregate to generate a polysiloxane coupling layer, forming chemical adsorption, hydrogen bonds and covalent bonds; the flexible organic-philic end and azide functional group of the azide coupling monomer are simultaneously modified on the surface of the fine aggregate; Step 4: Using Cu(Ⅰ)-catalyzed alkynyl-azide cycloaddition click reaction, the fine aggregate is modified onto the surface of the coarse aggregate to prepare the premixed aggregate; Step 5: Heat the high-viscosity modified asphalt to 160-180°C, add the premixed aggregate, mix for 60-120 seconds, then add the mineral powder, mix for 45-70 seconds, and obtain high-viscosity asphalt concrete with more crushed stone; The synthesis method of the alkynyl coupling monomer comprises: using triethoxysilane and undecenyl alcohol as raw materials and chloroplatinic acid as a catalyst to synthesize hydroxytriethoxysilane through a hydrosilylation reaction; using the Williamson ether synthesis method, 3-bromopropyne and hydroxytriethoxysilane undergo an etherification reaction catalyzed by sodium hydride to prepare the alkynyl coupling monomer; The synthesis method of the azide coupling monomer is as follows: using the Williamson ether synthesis method, 1,4-dibromobutane and hydroxytriethoxysilane undergo an etherification reaction catalyzed by sodium hydride to generate bromotriethoxysilane; based on the nucleophilic substitution reaction mechanism, bromotriethoxysilane is used as a raw material to undergo an azidation reaction with sodium azide to prepare the azide coupling monomer; The preparation method of the catechol-terminated cross-linking monomer comprises: utilizing the Schiff base reaction mechanism, using 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane as a raw material, and using 3,4-dihydroxybenzaldehyde as a capping agent to prepare the catechol-terminated cross-linking monomer.
2. The high-viscosity asphalt concrete with more crushed stones according to claim 1, characterized in that: The mineral aggregate grading ratio in the high-gravel high-viscosity asphalt concrete is: coarse aggregate with a particle size of 4.75mm~16mm: fine aggregate with a particle size of 0.075mm~4.75mm: mineral powder = 63%: 31.9%: 5.1%.
3. The high-viscosity asphalt concrete with more crushed stones according to claim 1, characterized in that: The oil-to-stone ratio in the high-viscosity asphalt concrete with high crushed stone content is 6.
0.
4. Application of a high-viscosity asphalt concrete with high crushed stone content according to any one of claims 1 to 3 in pavement engineering.
Citation Information
Patent Citations
Compound modified asphalt mixture
CN107200512A
Anti-skid surface layer of asphalt pavement and construction method of anti-skid surface layer
CN116640455A